A improvisação vocal na Copacabana dos anos 50 a 70 - Glawcer Nader Saraiva Ferreira Félix (2020)
This study aims to research and analyze historical-musical processes through which jazz improvisational vocal improvisation, in the time frame to which this work is dedicated, took place in Brazil. After a contextualization on the relations between instrumental music and music sung in jazz, from NESTROVISKI (2013), improvisation; where music is intimately articulated with the concept of language, using MONSON's (1996) studies as a basis, we approach how the elements of jazz were incorporated into improvisation in Brazilian popular music, in addition to the historical-social context that brings them together; the Afro religious origin of the styles listed here, VENTURA (1985) and SANDRONI (2001). Finally, we pass the transcription of the excerpts of the performances Fim de caso (Dolores Duran, 1958); Influência do Jazz (Leny Andrade, 1963); Time after Time (Wilson Simonal and Sarah Vaughan, 1970); Rosa Morena (Elis Regina and Wilson Simonal, 1971) and Falsa Baiana (Gal Costa, 1971) and their respective musical analyzes, based on the concepts of ALMADA (2000) and COKER, CASALE, CAMPBELL & GREENE (1970). We found a very significant jazz influence on vocal improvisation in Brazilian music performed between the 50s and 70s in Copacabana. And even though here, vocal improvisation along the lines of scat singing did not take place in a totally natural way, such improvisation found performers who were dedicated to spreading the style by rubbing samba and jazz, in a solid and cohesive junction.